PENGGUNAAN MEDIA PEMBELAJARAN KEARIFAN LOKAL DAN MOTIVASI BELAJAR UNTUK MENINGKATKAN HASIL BELAJAR - Titi Solihati (Journal of Education Papua Baru, 2022)
This article was created to find out how much the use of local wisdom learning media and learning motivation to improve learning outcomes. Learning media is an intermediary tool or messenger used by educators/teachers in conveying teaching material to students in the hope of increasing students' interest in learning and being able to acquire knowledge, skills or attitudes. There are many local wisdom media that we can use such as seeds, grains, rocks, fruits, leaves and so on, teachers can easily teach and guide students and are also very helpful for students in participating in the learning process in class and outside the classroom thus the motivation that students feel will continue to increase and be more enthusiastic, and students get better learning outcomes and experience improvements according to the expectations of all parties. Teachers and students together use local learning media around it, it is hoped that the teaching and learning process will run smoothly and can improve learning outcomes. With the identified and validated local wisdom, it is hoped that it will make it easier for teachers to use it in learning and for students it is hoped that it will be easier for students to understand learning material, so that student learning outcomes experience an increase as expected.Keywords: Local wisdom media, motivation and learning outcomes.